How deeply held are anti-American attitudes among Pakistani youth? Evidence using experimental variation in information - Adeline Delavande; Basit Zafar (Federal Reserve Bank of New York, 2012)
This paper investigates how attitudes toward the United States are affected by the provision of information. We use an experimentally generated panel of attitudes, obtained by providing urban Pakistanis with fact-based statements describing the United States in either a positive or negative light. Anti-American sentiment is high and heterogenous in our sample at the baseline. We find that revised attitudes are, on average, significantly different from baseline attitudes, indicating that providing information had a meaningful effect on U.S. favorability. Observed revisions are a consequence of both the salience of already known information and information acquisition that leads to a convergence in attitudes across respondents with different priors. This analysis provides evidence that (i) public opinions are not purely a cultural phenomenon and are malleable, and (ii) the tendency of respondents to ignore information not aligned with their priors can be overcome. Our findings make the case for dissemination of accurate information about various aspects of the Pakistan-U.S. relationship in order to improve opinion toward the United States.
Keywords: D83; L80; 330; attitudes; information; anti-Americanism; media